The 2 week urgent referral pathway for suspected cancer: the paediatric experience in a local oncology shared-care centre. (4th April 2011) - Mant, J E; Nanduri, V; Francis, D
Abstract : Aims: In 2000, the Department of Health published the National Health Service Cancer Plan. This stipulated that all patients with suspected cancer, including children, should be seen by a specialist within 2 weeks of referral by a general practitioner. The benefit of this 2-week referral pathway has been questioned in the adult population because many of those referred do not have cancer and many cancer patients are not referred via the 2-week wait route. We aimed to find out whether this is also the case in children. We therefore reviewed the referral pathway of all children diagnosed with cancer since 2007 at a District General Hospital offering a shared-care oncology service. Methods: A database of all children referred via the 2-week wait pathway as well as all children diagnosed with cancer via other means is maintained by the shared care oncology centre. The notes of all children referred between January 2007 and July 2010 were retrospectively reviewed. Results: Over the 3½ year period, 49 children aged 0–15 years were newly diagnosed with cancer. Only one of these children was referred via the 2-week wait pathway. In the same period, 35 children were referred via the 2-week wait pathway. The primary reasons given for referral were: headache (n=7), enlarged lymph nodes (n=16), absent red reflex (n=2), abnormal mass (n=7), skin abnormality (n=1), and abnormal blood results (n=2). The referral outcome is shown in table 1 . The one child with cancer had a Wilm's tumour. Two other children were referred to the Paediatric Oncology Specialist centre for further investigations but were found to have a non-malignant condition. Most children (32/35) did not require any specialist paediatric oncology input, 49% (17/35) required no further investigations and 40% (15/35) were discharged from care at the first appointment. Conclusions: The 2 week referral pathway is not effective in facilitating early diagnosis and treatment of children with cancer. Few children referred have cancer and those with cancer are being referred via different means.